2011
DOI: 10.1080/13691058.2010.529945
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio-cultural context on young people's condom use: evidence from two Pacific Island countries

Abstract: Young people are a key group for HIV prevention in the Pacific region where levels of STIs are high and condom use is low. During 2008, 62 in-depth interviews were conducted with people aged between 18 and 25 years in Tonga and Vanuatu. The research was aimed at understanding factors impacting on young peoples' condom use in two Pacific Island nations. The data show a marked disjuncture between attitudes and practice with regard to condoms. This paper discusses factors underpinning that inconsistency and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…The perception that condom use could signify a breach of trust in sexual partnerships, thereby negating condom use, has been highlighted in other studies as well (Aube-Maurice et al 2012; Dhapola et al 2007; McMillan and Worth 2011; Puri and Cleland 2006). Additionally, as reported elsewhere (Aube-Maurice et al 2012), Indian culture is characterised by complex gender-based power dynamics, which could influence condom use in such partnerships, particularly in instances where male migrants provide gifts to their sexual partners.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The perception that condom use could signify a breach of trust in sexual partnerships, thereby negating condom use, has been highlighted in other studies as well (Aube-Maurice et al 2012; Dhapola et al 2007; McMillan and Worth 2011; Puri and Cleland 2006). Additionally, as reported elsewhere (Aube-Maurice et al 2012), Indian culture is characterised by complex gender-based power dynamics, which could influence condom use in such partnerships, particularly in instances where male migrants provide gifts to their sexual partners.…”
Section: Discussionmentioning
confidence: 89%
“…These factors include community norms and practices (McCreary et al 2008; Soskolne and Shtarkshall 2002), traditional gender roles and gender power inequalities (Gupta 2002; McCreary et al 2008), stigma and discrimination (Nguyen et al 2012) and low education status (Ordóñez and Marconi 2012). Research in different settings shows that social and cultural norms, including those condoning gender inequities and male dominance, shape sexual interactions such as types of sexual relationships (non-spousal/premarital/transactional), the frequency of and opportunities for sexual contact, and condom use (Halli et al 2007; Parker 2001; McCreary et al 2008; McMillan and Worth 2011). Prevailing traditional gender norms allow men greater sexual freedom, opportunity and mobility than women, and condone multiple sexual partnerships (Gupta 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The taboos related to a married couple's sexuality (Kakar and Kakar 2007) are significant in the Indian cultural context and also appear, in our study, to lead to buying sex and asking for culturally unacceptable practices. These considerations underlie the importance of the social and cultural context when developing HIV-prevention programmes, as also suggested McMillan and Worth (2011).…”
Section: Discussionmentioning
confidence: 97%
“…This general attitude may be a barrier to addressing the association between intimate relationships and psychological distress. Research with young Pacific people has revealed a secretiveness around sexual relationships due to a fear of judgment from their family and wider community (McMillan and Woth, 2010;University of Auckland, 1999). Adequate sexual expression is a vital part of intimate human relationships and has the capacity to enhance quality of life by providing a sense of physical, psychological, and social well-being.…”
Section: Croftmentioning
confidence: 98%